Dietary Energy and Protein Requirements of Lesser Mouse Deer (Tragulus Ja Vanicus) in Captivity - Darlis (2001)
A series of experiments was conducted to study various aspects of nutrition of lesser mouse deer to determine their dietary energy and protein requirements for maintenance and growth in captivity. When given a choice of feeds male mouse deer preferred sweet potato, while the female preferred carrot in terms of fresh weight. However, in terms of dry matter (OM) intake, the rabbit pellet (90% OM) was consumed the most by both male and female mouse deer. The daily intakes of OM, organic matter (OM) and gross energy (GE) were significantly (P<0.05) higher in male than female when given these feeds, but the OM intake was similar when they were fed only rabbit pellet. The crude protein (CP) intake was similar between male and female -mouse deer when fed various types of feed or only pellet. The ability of male and female mouse deer to digest OM, OM and GE of feed were also similar. In the energy expenditure and activity study, it was observed that both male and female mouse deer spent most of their time sitting (926.0 min/d), followed by standing (491.5 min/d) and eating (22.5 min/d). Heat production (HP) for male and female (0 .44 and 0.43 kJ/kg WO 75/min, respectively) was the highest during eating followed by standing (0.37 and 0.33 kJ/kg WO 75/min, respectively) and sitting (0.26 and 0.26 kJ/kg WO 75/min, respectively). The HP for morning to afternoon and afternoon to evening periods were significantly higher than the night and early morning periods . The overall HP of males during morning to afternoon and afternoon to evening periods was significantly (P<0. 05) higher than that of females. When the mouse deer were fed diets containing 5% to 20% of fiber, the digestibility values of DM, OM, CP and GE were significantly (P<0.05) decreased with an increase in fiber level . Positive nitrogen balance and body weight gain was obtained when the levels of fiber were in the range of 5% - 1 0%. The passage rate constants of solid and fluid were significantly increased when more than 10% fiber was in the diet. On the other hand, the mean retention time of solid and fluid decreased with increasing levels of fiber in the diet. Metabolisable energy requirements for maintenance in growing and mature mouse deer were in the range of 418.0 kJ/kg WO 75/d - 424.9 kJ/kg WO 75/d. Efficiency of utilisation of energy requirement for maintenance was 0.52 for growing mouse deer and 0.44 for mature mouse deer. Maximum nitrogen balance was achieved at 20% metabolisable energy above maintenance. The protein requirement for maintenance of growing male, mature male and mature female was 0.33, 0.25 and 0.28 g N/kg W0 75/d or 6.4%,5.4% and 5 .3% CP in the diet, respectively and for growth was 0.93 , 0.94 and 0.98 g N/kg W075/d or 18.2%,18.8% and 18.7% CP in the diet, respectively.